Chromosomal imbalances are uncommon in chagasic megaesophagus - Bellini, Marilanda F. [UNESP]; Manzato, Antonio J. [UNESP]; Silva, Ana E. [UNESP]; Varella-Garcia, Marileila (Biomed Central Ltd., 2010)
Background: Chagas' disease is a human tropical parasitic illness and a subset of the chronic patients develop megaesophagus or megacolon. The esophagus dilation is known as chagasic megaesophagus (CM) and one of the severe late consequences of CM is the increased risk for esophageal carcinoma (ESCC). Based on the association between CM and ESCC, we investigated whether genes frequently showing unbalanced copy numbers in ESCC were altered in CM by fluorescence in situ (FISH) technology.Methods: A total of 50 formalin-fixed, paraffin-embedded esophageal mucosa specimens (40 from Chagas megaesophagus-CM, and 10 normal esophageal mucosa-NM) were analyzed. DNA FISH probes were tested for FHIT, TP63, PIK3CA, EGFR, FGFR1, MYC, CDKN2A, YES1 and NCOA3 genes, and centromeric sequences from chromosomes 3, 7 and 9.Results: No differences between superficial and basal layers of the epithelial mucosa were found, except for loss of copy number of EGFR in the esophageal basal layer of CM group. Mean copy number of CDKN2A and CEP9 and frequency of nuclei with loss of PIK3CA were significantly different in the CM group compared with normal mucosa and marginal levels of deletions in TP63, FHIT, PIK3CA, EGFR, CDKN2A, YES and gains at PIK3CA, TP63, FGFR1, MYC, CDNK2A and NCOA3 were detected in few CM cases, mainly with dilation grades III and IV. All changes occurred at very low levels.Conclusions: Genomic imbalances common in esophageal carcinomas are not present in chagasic megaesophagus suggesting that these features will not be effective markers for risk assessment of ESCC in patients with chagasic megaesophagus.